(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe clinical characteristics and evaluate the prognostic value of ALBI, EZ-ALBI, and PALBI scores in predicting rebleeding risk in patients with upper gastrointestinal bleeding due to esophageal variceal rupture. Subject and methods: A cross-sectional study with analytical components was conducted in 81 patients with upper gastrointestinal bleeding due to esophageal variceal rupture at Ca Mau General Hospital from June 2025 to January 2026. Results: Males accounted for 63.7%, with a mean age of 57.0 ± 11.9 years. Prior variceal bleeding was reported in 9.9%. Common comorbidities included hypertension (24.7%), diabetes (13.6%), hepatitis B (11.1%), and hepatitis C (3.7%). The rebleeding rate was 6.2%. ALBI and PALBI stratifications differed significantly by rebleeding outcome (p < 0.001), whereas EZ-ALBI did not (p = 0.073). Rebleeding clustered in higher ALBI (grades 2-3) and PALBI groups. On ROC analysis, ALBI showed the highest discrimination (AUC 0.879), followed by PALBI (0.845) and EZ-ALBI (0.834). Conclusion: ALBI and PALBI demonstrated useful risk stratification and predictive performance for rebleeding, with ALBI showing a trend toward better discrimination, while EZ-ALBI showed no significant association.